(untitled) (Journal of Imam Al-Kadhim College, 2024)
Abstract: Women in the United States of America played an important role in the legislative authority, especially after women gained the right to vote in the 1920s. A number of them were elected as members of Congress and represented an important segment of the American people. Among these women was Patsy Takimoto Mink, the first American of American descent. An Asian woman who reached Congress, her brilliance and leadership qualities began early in her life. She was elected president of the student body of Hawaii High School in 1943. She also fought in her youth against racial segregation at the university and obtained a degree in zoology and chemistry from the University of Hawaii in 1943. 1948 and obtained a law degree from the University of Chicago in 1951. She joined the Democratic Party and was able to obtain a seat in the Hawaiian Territory Legislative Council in 1956. In 1964, she was elected to the US House of Representatives and served there for two separate terms, the first (1964-1976) and the second. (1990-2002) She contributed to legislating a number of laws and had firm political positions in the US Congress.